Economic reform in China : a new phase - Tseng, Wanda...[et al] (IMF WashingtonUS, 1994)
Discusses the current reform programme in China. Focuses on aspects relating to macro-economic management viz. exchange and trade system reforms, monetary policy and finiancial sector reforms, fiscal system reforms, investment system reform and state enterprise reform.